Energy loss of protons in hydrogen plasma. (13th February 2018) - Cheng, R.; Zhou, X.; Wang, Y.; Lei, Y.; Chen, Y.; Ma, X.; Xiao, G.; Zhao, Y.; Ren, J.; Huo, D.; Peng, H.; Savin, S.; et al.
Abstract: This paper reports the measurement of the energy loss of protons at the energy of 100 keV penetrating a partially ionized hydrogen plasma. The plasma of ne ≈ 10 15–16 cm −3 ; Te ≈ 1–2 eV and lifetime of about 8 µs is created by the hydrogen gas discharge. The experimental results show an increase of a factor of 2.8 in the energy loss, which are in good agreement with the Bethe, Standard Stopping Model, Li–Petrasso and Vlasov models' predictions within the error limit. The Bethe–Bloch Coulomb logarithm term is found to increase by a factor of 4.0 for free electrons as compared with the situation where bound electrons prevail. The potential application of protons energy loss for diagnosing the electron density in plasma is proposed too.